THE UTILIZATION OF AI FOR BUSINESS ANALYSIS OF CONSUMER BEHAVIOR AND BUSINESS COMMUNICATION IN MARKETING MANAGEMENT: A STUDY ON THE PUTRI RIVER TOURISM WEBSITE IN SUMEDANG - Yuyun Yuniarsih; Anita Syafariah; Abyan Faliq Athallah; Rafly Ramadhany (PT Altin Riset Publishing, 2026)
Digital transformation in the tourism industry urges business actors to adopt technologies that enhance both customer experience and operational efficiency. This study aims to analyze the utilization of artificial intelligence (AI) in interpreting consumer behavior, managing business communication, and improving the effectiveness of digital marketing management on the local tourism platform Puteri River Inn Sumedang. The method used is descriptive qualitative, involving non-participant observation, document study, and content and thematic analysis of digital data from websites, social media, and user reviews. The results indicate that although direct AI implementation is not yet visible on the platform, the potential for application is significant. AI can be utilized to analyze consumer preferences regarding lodging, culinary options, and entertainment facilities such as flying fox, swimming pool, and camping. Business communication could be enhanced through chatbots, automated reservation systems, and personalized digital promotions. From a marketing management perspective, AI supports more effective STP strategies (segmenting, targeting, and positioning) using real-time data. This study concludes that AI-based digitalization of local tourism is a strategic step toward strengthening competitiveness and increasing visitor satisfaction. Strong managerial commitment and technological support are essential to realize this transformation.